Management Control System in Higher Education Institutions and Its Role on Performance: Does Gender Matter? - Sofyani, Hafiez; Puji Utami , Tiyas; Yani, Indah (APSSAI ACCOUNTING REVIEW, 2024)
Research aims: This study examines the effect of management control system (MCS) implementation consisting of three dimensions: input, output, and behavioural, on the performance of study programs in private Higher Education Institutions (HEIs). Also, this study tests whether there is a moderating impact of gender. Design/Methodology/Approach: This study uses a questionnaire survey approach and statistical hypothesis testing. The population of this study is permanent lecturers at private HEIs in Indonesia who and are subject to the MCS policy. Meanwhile, the SEM-PLS technique was used to test the hypothesis. Research findings:  Involving 291 lecturers as samples, this study found that in overall data, output and behavioural controls had a positive effect on performance, while input controls did not. The results of moderation testing using a split sampling indicated that in the Male group only behavioural control had a positive influence on performance. Meanwhile, in the female group, behaviour and output control influence performance. In other words, gender moderates the relationship between output control and performance, which means that output control needs to be emphasized more in women. Theoretical contribution/Originality: This study presents a new discussion on how MCS policies aimed at improving the performance of HEIs need to pay attention to gender issues. Practitioner/Policy implication: In fact, women and men have different ways of working and levels of sensitivity in responding to certain information and policies. Therefore, in the case of implementing MCS in HEIs, slight differences in treatment regarding gender differences are needed to make MCS have an optimal impact on performance.